# math

posted by .

Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find a similar equation for (a - b)2. Examine his argument.
(a - b)2 = [a + (-b)]2
= a2 + 2a(-b) + (-b)2
= a2 – 2ab + b2

• math -

He is correct.

## Similar Questions

1. ### math

Mike makees the following table of the distances he travels during the first day of the trip. A suppose Mike continues riding at this rate. Write an equation for the distance mike travles after t hours. B sketch a graph of the equation. …
2. ### Math-Algebra

Review examples 2, 3,and 4 in section 8.4 of the text. How does the author determine what the first equation should be?
3. ### Algebra

Why does this happen? A=3 and b=2 A+b=c is the equation. Multiplying both sides of the equation makes the equation a^2+2ab+b^2 which is equal to a^2+ab-ac=-ab-b^2+bc Dividing by (a+b-c) we find a=-b or 3=-2 Why?
4. ### math

Review examples 2, 3, and 4 in section 8.4 of the text. How does the author determine what the first equation should be?
5. ### algebra

Review examples 2, 3, and 4 in section 8.4 of the text. How does the author determine what the first equation should be?
6. ### Chemistry

For each reaction, complete and balance the equation and give the net ionic equation. a) KOH(aq)+ZnCl2(aq)-> KCl2+ZnOH The second half of the equation is how i had done on the exam but he said its not balanced. How do I balance …
7. ### math 213

Kahlil said that using the equation he can find a similar equation for Examine his argument. If it is correct, supply any missing steps or justifications; if it is incorrect, point out why. = a2 - 2ab + b2 = a2 + 2a1-b2 + 1-b22 1a …
8. ### math

Kahlil said that using the equation € (a + b)2 = a2 + 2ab + b2, , he can find a similar equation for € (a − b)2 . Examine his argument. If it is correct, supply any missing steps or justification; If it is incorrect point …
9. ### Math using Quadratic equation

The area of a square is 196cm2(squared), find the measure of one side. Thank you,, this is my assign. In math1, im using the formula A=s*s but i need to solve this using quadratic equation.
10. ### Polynomials

State whether the following equations are sometimes, always or never true. a) a^2-2ab-b^2= (a-b)^2, bis not equal to 0 b) a^2+ b^2= (a+b)(a+b) c) a^2-b^2= a^2-2ab+b^2 d) (a=b)^2 = a^2+2ab+b^2 I don't understand what these questions …

More Similar Questions